2013
DOI: 10.2478/pjct-2013-0075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on ZSM-5 catalyst for methanol to propylene conversion

Abstract: B-ZSM-5 catalysts were prepared by various modifi cation methods with boric acid, including ion-exchange, impregnation and direct synthesis. The catalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), NH 3 -Temperature Programmed Desorption (NH 3 -TPD), N 2 adsorption-desorption, Fourier Transform Infrared spectrometry (FT-IR), 27 Al and 11 B MAS NMR spectra. The results revealed that the weak acidity of catalysts was signifi cantly increased by modifi cation. The catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Catalytic activity tests, in most cases, are performed using fresh catalysts at raw material conversion near to 100% [15,16]. The selectivity of product formation was estimated for fresh catalyst at zero time on stream (i.e., initial selectivity) [4,17,18]. However, the activity of the fresh catalyst that is estimated based on conversion of raw material to hydrocarbons, decreases during the reaction due to blocking of Brønsted acid sites by coke.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic activity tests, in most cases, are performed using fresh catalysts at raw material conversion near to 100% [15,16]. The selectivity of product formation was estimated for fresh catalyst at zero time on stream (i.e., initial selectivity) [4,17,18]. However, the activity of the fresh catalyst that is estimated based on conversion of raw material to hydrocarbons, decreases during the reaction due to blocking of Brønsted acid sites by coke.…”
Section: Introductionmentioning
confidence: 99%
“…The acidity of catalyst plays an important role in catalytic activity through MTO reaction, and acid adjustment is the most significant affecting factor for product distribution and catalytic stability [10][11][12][13][14][15][16][17][18]. Many methods could adjust the catalysts acid properties for a better catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The production of some Lewis acid sites in the structure of 2% Ba-ZSM-5 may correspond to the combination of promoter species with bridging hydroxyl groups and formation of extra-framework Al. 53−55 On account of the partial dealumination and formation of new Lewis acid sites, the literature review revealed that impregnation of some promoters such as Mg, 26 Mo, 54,55 B, 23 and Ni 47 increases the number of Lewis acid sites. This phenomenon can be explained by the interaction of the promoter with the framework Al atoms.…”
Section: Nh 3 -Tpd Analysismentioning
confidence: 99%
“…It is reported that, weak acidity not only contributes methanol to the DME reaction; it can also participate in the methylation/alkylation reaction cycle and produce light olefins (especially propylene). 22,23,48 The increase of weak acid site density can improve propylene production and has a positive effect on catalyst stability. 62 Likewise, the strength of strong acid sites of DZSM-5 decreases relative to HZSM-5, leading to an intensity reduction of secondary reaction performance and conversion decrement of light olefins to precursors of coke.…”
Section: %) and Light Olefins (6738%) And A Propylene/ethylene Ratmentioning
confidence: 99%
See 1 more Smart Citation